135k views
2 votes
Multiply
(4-3i)(-7 -2i)

2 Answers

3 votes

Answer: -9i

Explanation:

1) subtract 4 - 3i which equals 1i

2) subtract -7 -2i which equals -9i

3) multiply 1 x -9 which equals -9i

User DavidColson
by
5.1k points
5 votes

Answer:

= -34 + 13i

Explanation:

Given that:

= (4-3i)(-7 -2i)

By simplifying

= 4(-7 - 2i) - 3i(-7 - 2i)

"-" sign befor bracket will alter the inner signs

= -28 - 8i + 21i + 6i^2

As i^2 = -1

= -28 + 13i + 6(-1)

= -28 + 13i -6

= -34 + 13i

i hope it will help you!

User Kyun
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.